Implementasi Big Data Di Media Sosial Sebagai Strategi Komunikasi Krisis Pemerintah - Muhammad Dimas Aldy; Muhammad Irwan Padli Nasution (Universitas Katolik Widya Karya Malang, 2023)
This study aims to describe the implementation of big data on social media in carrying out crisis communication. This study uses a qualitative approach, with data collection techniques through literature study. Literature study is a literature review with a traditional-conceptual approach. The results of this study also emphasize three aspects, namely: 1). The government must define a crisis because to understand a crisis, of course, we must start by defining it first. Each crisis that arises is accompanied by its own characteristics. 2). The government can use Big Data information sources to accelerate the implementation of government programs. 3). One of the efforts to look at big data to identify problems is to carry out the stages of social media. In the era of advances in communication and information technology, the existence of social media can no longer be separated from the activities of the world community.